ସାରଳା ମହାଭାରତ - Sarala Das (Sarala Sahitya Sansad, 2022)
Sarala Mahabharat is the first National Epic of Odia literature, is different from original Sanskrit Mahabharat in many ways. A Sudra Saint, Sarala Das composed this Mahabharat with the blessings of Goddess Srala in 18 parbas, some are different from original Sanskrit Mahabharat. He added Parbas like Madhya, Gada, and Kainshika, and dropped Sauptika, Anusashana and Mahaprasthanika parbas of Sanskrit Mahabharat. Many popular legends and anecdote have taken place in Sarala Mahabharat in one way and in other way many legends, proverbs also originated from it. This Epic is a picture gallery of Odia social life to make his motherland, Odisha loom,large and important in the eyes of his compatriots with the Holy halo of Puranic sanctity, he not only linked Srikrishna’s death in Dwaraka to the rise of Jagannath at Puri, but also he brought the Pandavas to visit all sacred places of Odisha and live like common Odia citizen. Sarala the pageant genius not only wrote a great Epic but practically created a whole literature. The entire development of Odia literature was possible just because this pageant poet left behind this grand composition in a language. That was still contemptible in the eyes of the learner his successful adventure provided inspiration and encouragement to all his immediate successor.
Sarala Mahabharata
Keywords: Odia